Pragmatics of the political speech - haddadou., yasmina (Journal of Social Sciences and Humanities, 2024)
This study aims to approach theoretically about the interrelationship between pragmatics as an analytical approach and political speech as a discourse with a pragmatics function. The various rhetorical strategies, focusing on several elements: the nature of political speech, the definition of the pragmatics approach, the linguistic analysis of discourse according to the theory of speech acts by SEARLE, and finally the intentionality. Highlighting in this the importance of the pragmatics approach in analyzing political discourse, specifically the speech acts theory of SEARLE, according to its three levels ( locutionary act, propositional act, illocutionary act) Where we concluded that the theory is suitable for linguistic behavioral analysis of various types of discourse, and political discourse in particular - as it is an intentional discourse that adopts multiple strategies - and from it reaching the semantic level by standing on the purposes of the political communicator, an approach that constitutes the crossroads of several sciences (communication science, linguistic, political science...)